Bypassing Iron Storage in Endodermal Vacuoles Rescues the Iron Mobilization Defect in the natural resistance associated-macrophage protein3natural resistance associated-macrophage protein4 Double Mutant . Issue 1 (31st July 2015) - Mary, Viviane; Schnell Ramos, Magali; Gillet, Cynthia; Socha, Amanda L.; Giraudat, Jérôme; Agorio, Astrid; Merlot, Sylvain; Clairet, Colin; Kim, Sun A.; Punshon, Tracy; Guerinot, Mary Lou; Thomine, Sébastien
Abstract : Mutations in vacuolar iron transporters modify both tissue specific and subcellular localization of seed iron stores. Abstract: To improve seed iron (Fe ) content and bioavailability, it is crucial to decipher the mechanisms that control Fe storage during seed development. In Arabidopsis ( Arabidopsis thaliana ) seeds, most Fe is concentrated in insoluble precipitates, with phytate in the vacuoles of cells surrounding the vasculature of the embryo. NATURAL RESISTANCE ASSOCIATED-MACROPHAGE PROTEIN3 (AtNRAMP3) and AtNRAMP4 function redundantly in Fe retrieval from vacuoles during germination. When germinated under Fe -deficient conditions, development of the nramp3nramp4 double mutant is arrested as a consequence of impaired Fe mobilization. To identify novel genes involved in seed Fe homeostasis, we screened an ethyl methanesulfonate-mutagenized population of nramp3nramp4 seedlings for mutations suppressing their phenotypes on low Fe . Here, we report that, among the suppressors, two independent mutations in the VACUOLAR IRON TRANSPORTER1 ( AtVIT1 ) gene caused the suppressor phenotype. The AtVIT1 transporter is involved in Fe influx into vacuoles of endodermal and bundle sheath cells. This result establishes a functional link between Fe loading in vacuoles by AtVIT1 and its remobilization by AtNRAMP3 and AtNRAMP4. Moreover, analysis of subcellular Fe localization indicates that simultaneous disruption of AtVIT1, AtNRAMP3, and AtNRAMP4 limits Fe accumulation in vacuolar globoids.